Cerium-based abrasive slurry stock solution and method for manufacturing the same, and abrasive liquid

KR103018392B1Active Publication Date: 2026-09-11RESONAC CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
KR1020227035630
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-27
Filing Date
2021-03-24
Publication Date
2026-09-11
Estimated Expiration
2041-03-24

Smart Images

  • Figure 112022107657510-PCT00001
    Figure 112022107657510-PCT00001
Patent Text Reader

Abstract

The present invention provides a cerium-based abrasive slurry stock solution having good polishing performance for glass materials and excellent productivity, a method for manufacturing the same, and a polishing liquid. The cerium-based abrasive slurry stock solution of the present invention is a cerium-based abrasive slurry stock solution comprising mixed rare earth oxide particles and water, wherein the cerium-based abrasive slurry stock solution comprises an anionic water-soluble polymer and a phosphate compound, wherein the oxide equivalent content of the total rare earth element (TREO) is 10.0 to 40.0 mass%, the oxide equivalent content of cerium in the TREO is 50.0 mass% or more, the content of the anionic water-soluble polymer is 1.5 to 10.0 mass parts per 100 mass parts of the TREO, and the particle diameter (D50) at 50% of the cumulative volume in the particle size distribution by laser diffraction scattering of the slurry particles is 0.10 to 0.35 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a cerium-based abrasive slurry stock solution used for polishing glass materials such as liquid crystal panels, hard disks, glass substrates used for specific frequency cut filters, and glass substrates for optical lenses, a method for manufacturing the same, and a polishing liquid. Background Technology

[0002] Glass materials are used for a wide variety of applications, and depending on the use, surface polishing may be required. In particular, glass materials such as glass substrates used in liquid crystal panels, hard disks, and filters for specific frequency cuts, as well as glass substrates for optical lenses, require surface polishing processing with high smoothness and high efficiency.

[0003] In surface polishing of glass materials requiring such excellent polishing performance, cerium-based abrasives such as those described in Patent Document 1 or Patent Document 2 are widely used.

[0004] In addition, as the demand for high precision of the polished surface of glass materials increases, there is a growing demand for fine-grained cerium-based abrasive slurries (polishing liquids) to reduce the surface roughness of glass materials and make them smoother. Prior art literature

[0005] International Publication No. 2019 / 049932 Japanese Patent Publication No. 2019-208029 The problem to be solved

[0006] However, when the particles in the cerium-based abrasive slurry become fine, it becomes difficult to maintain the polishing speed or smoothing power, and there were cases where the polishing performance on glass materials deteriorated. In addition, there was a problem in that the productivity of the cerium-based abrasive slurry stock solution decreased, leading to an increase in the manufacturing cost of the said slurry stock solution.

[0007] Therefore, there is a demand for a cerium-based abrasive slurry stock solution that can maintain a high level of polishing speed and smoothing power for glass materials, and furthermore, suppresses manufacturing costs and has excellent productivity.

[0008] The present invention was made to solve the above-mentioned problems and aims to provide a cerium-based abrasive slurry stock solution having good polishing performance on glass materials and excellent productivity, a method for manufacturing the same, and a polishing liquid. means of solving the problem

[0009] The present invention is based on the discovery that, in a cerium-based abrasive slurry using mixed rare earth oxide particles as abrasive particles, good polishing performance is obtained by using a predetermined amount of anionic water-soluble polymer and a phosphate compound in combination, and that a stock solution of a cerium-based abrasive slurry (polishing liquid) having good polishing performance can be produced with high productivity.

[0010] That is, the present invention provides the following [1] to [8].

[0011] [1] A cerium-based abrasive slurry stock solution comprising mixed rare earth oxide particles and water, wherein the cerium-based abrasive slurry stock solution comprises an anionic water-soluble polymer and a phosphate compound, the oxide equivalent content of the total rare earth element (TREO) is 10.0 to 40.0 mass%, the oxide equivalent content of cerium in the TREO is 50.0 mass% or more, the content of the anionic water-soluble polymer is 1.5 to 10.0 mass parts per 100 mass parts of the TREO, and the particle size (D) at 50% of the cumulative volume in the particle size distribution by laser diffraction scattering of the slurry particles 50 ) is a cerium-based abrasive slurry stock solution with a thickness of 0.10 to 0.35 μm.

[0012] [2] A cerium-based abrasive slurry stock solution described in [1] above, having a fluorine atom content of 0.1 mass% or less.

[0013] [3] The cerium-based abrasive slurry stock solution described in [1] or [2], wherein the anionic water-soluble polymer is a polycarboxylic acid-based polymer.

[0014] [4] A cerium-based abrasive slurry stock solution in which the above polycarboxylic acid-based polymer is one or more selected from acrylic acid, copolymers of acrylic acid and maleic acid, and alkali metal salts thereof.

[0015] [5] The above phosphoric acid compound is one or more selected from tripolyphosphoric acid, pyrophosphoric acid and hexametaphosphoric acid, and alkali metal salts thereof, and is a cerium-based abrasive slurry stock solution described in any one of [1] to [4].

[0016] [6] A cerium-based abrasive slurry stock solution described in any one of [1] to [5], wherein the content of the above phosphoric acid compound is 0.5 to 10.0 parts by mass per 100 parts by mass of the above TREO.

[0017] [7] A method for manufacturing a cerium-based abrasive slurry stock solution described in any one of [1] to [6] above, comprising: a process of wet grinding a mixed raw material containing the mixed rare earth oxide particles, water, and the anionic water-soluble polymer to obtain a ground slurry; a process of wet classifying the ground slurry to obtain a classified slurry; and a process of adding water and the phosphoric acid compound to the classified slurry and mixing to obtain the cerium-based abrasive slurry stock solution.

[0018] [8] The cerium-based abrasive slurry stock solution described in any one of [1] to [6] above is an abrasive solution diluted with water, and the TREO is an abrasive solution in which the amount is 0.1 to 10.0 mass%. Effects of the invention

[0019] The cerium-based abrasive slurry stock solution of the present invention can provide an abrasive solution that has excellent productivity and also has good abrasive performance for glass materials.

[0020] In addition, according to the manufacturing method of the present invention, the cerium-based abrasive slurry stock solution can be suitably manufactured.

[0021] Accordingly, the polishing liquid obtained using the cerium-based abrasive slurry stock solution of the present invention can maintain good polishing performance for glass materials while suppressing manufacturing costs. Specific details for implementing the invention

[0022] Hereinafter, embodiments of the cerium-based abrasive slurry stock solution of the present invention, the method for manufacturing the same, and the abrasive liquid obtained using the cerium-based abrasive slurry stock solution will be described in detail.

[0023] [Cerium-based abrasive slurry concentrate]

[0024] The cerium-based abrasive slurry stock solution of the present embodiment is a slurry comprising mixed rare earth oxide particles and water, and comprises an anionic water-soluble polymer and a phosphate compound. The oxide equivalent content of total rare earth elements (TREO; abbreviation for Total Rare Earth Oxides) of the cerium-based abrasive slurry stock solution is 10.0 to 40.0 mass%, and the oxide equivalent content of cerium (CeO2) in the TREO (hereinafter referred to as "Ce amount") is 50.0 mass% or more. The content of the anionic water-soluble polymer in the slurry is 1.5 to 10.0 mass parts per 100 mass parts of the TREO. Furthermore, the cerium-based abrasive slurry stock solution has a particle size (D) at 50% of the cumulative volume in the particle size distribution by laser diffraction scattering of the slurry particles. 50 It is characterized by the fact that ) is 0.10 to 0.35 μm.

[0025] In addition, the term "cerium-based abrasive" in the present invention refers to an abrasive in which the oxide equivalent content of cerium relative to TREO in the abrasive is 50.0 mass% or more.

[0026] (Mixed rare earth oxide particles)

[0027] In the present embodiment, the term "mixed" in the mixed rare earth oxide particles means that multiple types of rare earth elements are included. The mixed rare earth oxide may include rare earth elements other than Ce. Examples of the rare earth elements listed are La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, etc.

[0028] The TREO in the above mixed rare earth oxide particles is preferably 80.0 mass% or more, more preferably 85.0 mass% or more, and even more preferably 90.0 to 100 mass%, from the perspective of improving the productivity of a cerium-based abrasive slurry stock solution suitable for surface polishing of glass materials.

[0029] In the same regard, the mixed rare earth oxide particles contain Ce as the main component among the total rare earth elements contained therein, and the amount of Ce in TREO (amount of Ce / TREO) is preferably 50.0 mass% or more, more preferably 60.0 mass% or more, and even more preferably 65.0 to 100 mass%.

[0030] In addition, TREO can be measured by oxalate precipitation, calcination, and gravimetric methods, and specifically by the method described in the examples below.

[0031] In addition, the content of each rare earth element, such as Ce, can be measured by instrumental analysis such as high-frequency inductively coupled plasma (ICP) analysis or fluorescence X-ray analysis, and in this embodiment, the value obtained by converting each rare earth element into an oxide from the measured value by ICP emission spectroscopic analysis (ICP-AES) is called the oxide equivalent amount.

[0032] The above-mentioned mixed rare earth oxides can be obtained by calcining, for example, mixed light rare earth compounds such as mixed rare earth carbonates, mixed rare earth monooxycarbonates, mixed rare earth oxalates, and mixed rare earth hydroxides. Furthermore, the term "mixed" as used herein is synonymous with the "mixed" of the mixed rare earth oxides described above.

[0033] As for the above mixed light rare earth compound, it is preferable that the content of impurities of non-rare earth components such as alkali metals, alkaline earth metals, and radioactive materials, and the content of heavy rare earth are reduced, and it is more preferable that Ce be the main component. As for the mixed light rare earth compound, for example, a mixed rare earth carbonate is preferably used in which TREO is 45 to 55 mass% and the amount of Ce in the TREO (amount of Ce / TREO) is about 65 mass%.

[0034] In addition, in this specification, "heavy rare earth" refers to a rare earth element with an atomic number greater than Pm, and rare earth elements other than heavy rare earth are referred to as "light rare earth."

[0035] The method for manufacturing mixed light rare earth compounds is not particularly limited. Mixed light rare earth compounds are obtained, for example, by separating and reducing the content of impurity components other than rare earth elements and heavy rare earths from ore containing rare earth elements through chemical treatment.

[0036] As for the ore containing rare earth elements, for example, rare earth concentrate obtained from raw ores such as natural monazite or bastnaesite containing a large amount of Ce is preferably used.

[0037] In the preparation of mixed light rare earth compounds, sulfuric acid roasting is a common chemical treatment method for reducing the content of impurity components. Sulfuric acid roasting is a method in which the crushed raw ore is roasted together with sulfuric acid to produce sulfates (rare earth sulfates), the sulfates are dissolved in water to form a rare earth sulfate solution, and insoluble impurity components are removed by filtration or the like. It is desirable that the content of impurity components in the mixed light rare earth compounds be reduced to 1.0 mass% or less.

[0038] In addition, as a chemical treatment method for reducing the content of heavy rare earths, for example, carbonate can be added to the rare earth solution of sulfuric acid after the above sulfuric acid roasting to form crude rare earth carbonate, hydrochloric acid is added to this to form a mixed rare earth chloride aqueous solution, and solvent extraction can be performed using an organic solvent. In solvent extraction, if necessary, the content of Ce and other light rare earths can be adjusted by using known methods such as adjusting the degree of extraction or using additives. It is desirable that the content of heavy rare earths in the mixed light rare earth compound be reduced to 1.0 mass% or less.

[0039] The mixed rare earth compound may include a mixed rare earth carbonate formed into a carbonate using sodium carbonate or ammonium bicarbonate, etc., and / or a mixed rare earth oxalate formed into an oxalate using oxalic acid, etc., after performing a treatment to reduce the content of impurity components.

[0040] When obtaining mixed rare earth oxides by calcining mixed light rare earth compounds, the calcination temperature is appropriately adjusted according to the composition of the mixed light rare earth compounds, but is preferably 600 to 1200°C, more preferably 700 to 1150°C, and even more preferably 800 to 1100°C. The calcination time is preferably 0.5 to 48 hours, more preferably 1 to 40 hours, and even more preferably 1.5 to 30 hours. The calcination atmosphere is preferably an atmospheric atmosphere.

[0041] The mixed rare earth oxide obtained by calcination is D measured by laser diffraction scattering method 50 These are preferably particles of 20 μm or less, more preferably 3 to 18 μm, and even more preferably 5 to 15 μm. Additionally, after firing, the particles may be crushed by a mechanical method to adjust them to the particle size of the above.

[0042] In addition, mixed rare earth oxide particles are commercially available, and commercially available products may be used as raw materials. Among the commercially available mixed rare earth oxide particles, there may be residual mixed rare earth carbonates, mixed rare earth monooxycarbonates, mixed rare earth oxalates, etc., which are the raw materials for their manufacture.

[0043] In the present embodiment, the cerium-based abrasive slurry stock solution preferably has a fluorine atom content of 0.1 mass% or less for the purpose of reducing the burden on the environment, more preferably 0.05 mass% or less, and even more preferably 0.01 mass% or less. If the fluorine atom content is 0.1 mass% or less, it is said that the cerium-based abrasive slurry stock solution substantially does not contain fluorine atoms.

[0044] In addition, the fluorine atoms that may be included in the cerium-based abrasive slurry stock solution of the present embodiment are considered to originate only from the mixed rare earth oxide particles, and the fluorine atoms originating from the anionic water-soluble polymer, phosphate compound, and water are considered to be 0 mass%. Accordingly, the fluorine atom content in the cerium-based abrasive slurry stock solution is estimated from the measured value of the fluorine atom content in the mixed rare earth oxide particles used in the manufacture of this slurry.

[0045] The fluorine atom content in the mixed rare earth oxide particles can be measured by alkaline melting of the mixed rare earth oxide particles to form an aqueous solution and by the ion electrode method.

[0046] (TREO)

[0047] The TREO in the cerium-based abrasive slurry stock solution of the present embodiment is derived from mixed rare earth oxide particles, and in terms of productivity and polishing performance, the TREO is 10.0 to 40.0 mass% in the cerium-based abrasive slurry stock solution, preferably 15.0 to 35.0 mass%, and more preferably 20.0 to 30.0 mass%.

[0048] (water)

[0049] The above cerium-based abrasive slurry stock solution is a slurry containing water, and water is used as a dispersion medium. In addition, from the perspective of the dispersibility of the slurry particles, it is preferable to use soft water or pure water.

[0050] As a dispersion medium, an aqueous dispersion medium other than water (e.g., water-soluble organic solvents such as alcohol, acetone, tetrahydrofuran, etc.) may be included to the extent that it does not impair the effects of the present invention, but it is generally preferable to have only water.

[0051] The water content in the above cerium-based abrasive slurry stock solution is an amount such that TREO is 40.0 mass% or less, and is appropriately adjusted according to the desired polishing process of the glass material. In terms of the uniform dispersion or viscosity of components other than water in the above cerium-based abrasive slurry stock solution, the water content in the above cerium-based abrasive slurry stock solution is preferably 60 mass% or more, more preferably 65.0 to 90.0 mass%, and more preferably 70.0 to 85.0 mass%.

[0052] (Anionic water-soluble polymer)

[0053] The anionic water-soluble polymer of this embodiment refers to a polymer that dissociates in ion-exchanged water to form a negatively charged ionic atmosphere and dissolves at least 10g per 100g of water at 25℃.

[0054] The above cerium-based abrasive slurry stock solution contains 1.5 to 10.0 parts by mass of an anionic water-soluble polymer per 100 parts by mass of TREO, more preferably 2.0 to 8.0 parts by mass, and even more preferably 2.2 to 5.0 parts by mass.

[0055] If the content of the anionic water-soluble polymer in the above cerium-based abrasive slurry stock solution is 1.5 parts by mass or more per 100 parts by mass of TREO, it is easy to prepare a homogeneous slurry, and the productivity of the cerium-based abrasive slurry stock solution is improved. Furthermore, if the above content is 10.0 parts by mass or less, the homogeneity of the slurry is easy to maintain, and it is easy to produce a cerium-based abrasive slurry stock solution with excellent productivity.

[0056] As for the above-mentioned anionic water-soluble polymer, polycarboxylic acid-based polymers and polysulfonic acid-based polymers are listed, for example, from the perspective that it is easy to obtain a homogeneous slurry by dispersing mixed rare earth oxide particles in water, and among these, polycarboxylic acid-based polymers are preferred. Among these, one type may be used alone or two or more types may be used in combination. Furthermore, the polycarboxylic acid-based polymer in this embodiment refers to a polymer in which, among 100 mol% of constituent monomer units, the monomer derived from an unsaturated carboxylic acid is 60 mol% or more.

[0057] The above-mentioned polycarboxylic acid-based polymers include, for example, poly(meth)acrylic acid, polyhydroxy(meth)acrylic acid, (meth)acrylic acid copolymers such as a copolymer of (meth)acrylic acid and maleic acid, copolymers of olefin and maleic acid, copolymers of alkylene oxide adducts such as ethylene oxide or propylene oxide of maleic acid and allyl alcohol, copolymers of allylsulfonic acid and maleic acid, etc., or alkali metal salts such as sodium salts and potassium salts thereof. Among these, polyacrylic acid, copolymers of acrylic acid and maleic acid, or alkali metal salts thereof are preferred, and copolymers of acrylic acid and maleic acid or alkali metal salts thereof are more preferred.

[0058] (Phosphoric acid compound)

[0059] The above cerium-based abrasive slurry stock solution contains a phosphoric acid compound together with the above anionic water-soluble polymer. By using the phosphoric acid compound in combination with the above anionic water-soluble polymer, good polishing performance on glass materials can be maintained in the polishing solution obtained by diluting the above cerium-based abrasive slurry stock solution.

[0060] The content of the phosphoric acid compound in the above cerium-based abrasive slurry stock solution is, in terms of maintaining good polishing performance of the polishing liquid on glass material, preferably 0.5 to 10.0 parts by mass, more preferably 0.8 to 8.0 parts by mass, and even more preferably 1.0 to 5.0 parts by mass with respect to 100 parts by mass of TREO.

[0061] The above phosphoric acid compounds include, for example, inorganic phosphoric acids such as tripolyphosphoric acid, pyrophosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, orthophosphoric acid, and phosphophosphate; organic phosphonic acids such as aminotrimethylenephosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, ethylenediaminetetramethylenephosphonic acid, and diethylenetriaminepentamethylenephosphonic acid; or alkali metal salts thereof such as sodium salts and potassium salts. These may be used alone or in combination of two or more. Among these, tripolyphosphoric acid, pyrophosphoric acid, hexametaphosphoric acid, or alkali metal salts thereof are preferred.

[0062] In addition, the above cerium-based abrasive slurry stock solution may have additives added as needed, such as pH adjusters, antifoamers, and rust inhibitors, within a range that does not interfere with the abrasive performance of the abrasive liquid prepared using it.

[0063] (D 50 )

[0064] The particle size of the slurry particles in the above cerium-based abrasive slurry stock solution is D 50 This is 0.10 to 0.35 μm, preferably 0.15 to 0.30 μm, and more preferably 0.17 to 0.28 μm.

[0065] The above D 50The value is obtained from the particle size distribution measured by the laser diffraction scattering method, specifically, the value measured by the MicroTrack particle size distribution meter described in the following example.

[0066] The above D 50 If this is 0.10㎛ or larger, the cerium-based abrasive slurry stock solution can be manufactured with good productivity. In addition, the above D 50 Since this is 0.35㎛ or less, the polishing surface can be smoothed well using the polishing liquid prepared using the above cerium-based abrasive slurry stock solution, making it easy to obtain excellent polishing performance.

[0067] [Method for manufacturing cerium-based abrasive slurry stock solution]

[0068] The cerium-based abrasive slurry stock solution of the present embodiment can be appropriately manufactured by the manufacturing method of the present embodiment, which comprises: a process (1) of wet grinding a mixed raw material comprising mixed rare earth oxide particles, water, and the anionic water-soluble polymer to obtain a ground slurry; a process (2) of wet classifying the ground slurry to obtain a classified slurry; and a process (3) of adding water and the phosphoric acid compound to the classified slurry and mixing them to obtain a cerium-based abrasive slurry stock solution.

[0069] Below, each process is explained in order.

[0070] (Process (1))

[0071] In process (1), a mixed raw material comprising mixed rare earth oxide particles, water, and the anionic water-soluble polymer is wet-ground to obtain a ground slurry.

[0072] With respect to the above mixed raw materials, by performing wet grinding with water as a dispersion medium, a homogeneous ground slurry can be efficiently produced while suppressing the thickening of the slurry.

[0073] The above wet grinding is preferably carried out using a medium mill, such as a ball mill or a bead mill, in order to obtain a homogeneous grinding slurry. As a dispersion medium, in order to improve dispersibility, a water-soluble organic solvent such as alcohol may be mixed and used in addition to water.

[0074] It is said that the above-mentioned mixed raw material has excellent productivity, as it allows for the production of a grinding slurry without hindering safe and stable grinding due to an increase in internal pressure and temperature of the mill, even when the concentration of mixed rare earth oxide particles is high, such as 50 mass% or more, in wet grinding using a bead mill.

[0075] The above wet grinding is performed in the subsequent process (2), where D of the slurry particles 50 In order to increase the yield of this classification slurry with a diameter of 0.10 to 0.35 μm, for example, when using a bead mill, it is preferable to obtain a ground slurry by using zirconia beads (bead diameter 0.1 to 0.5 mm) and grinding at a mill peripheral speed of 5 to 10 m / s.

[0076] (Process (2))

[0077] In process (2), the crushed slurry obtained in process (1) is wet-classified to obtain a classified slurry.

[0078] As described above, the above wet classification, in terms of obtaining a polishing liquid that exhibits good polishing performance for glass materials, involves D of the slurry particles in the cerium-based abrasive slurry stock solution. 50 This is performed so that it becomes 0.10 to 0.35 μm. In addition, D of the slurry particles in the above classification slurry 50 D of the slurry particles in the cerium-based abrasive slurry stock solution being manufactured 50 It can be considered almost equivalent to.

[0079] In the above wet classification, it is desirable to remove coarse particles with a particle size of at least 5.0 μm or more.

[0080] The above wet classification method is not particularly limited and can be performed using, for example, a liquid cyclone, a centrifugal settler, a slurry screener, etc.

[0081] (Process (3))

[0082] In process (3), water and the phosphoric acid compound are added to the classification slurry obtained in process (2) and mixed to obtain the cerium-based abrasive slurry stock solution.

[0083] In the cerium-based abrasive slurry stock solution of the present embodiment, the anionic water-soluble polymer and the phosphoric acid compound are used together, but if the phosphoric acid compound is added simultaneously with or first with the addition of the anionic water-soluble polymer, it is prone to significantly thickening when mixed to prepare the slurry. For this reason, in the present embodiment, the phosphoric acid compound is added later to the classification slurry to prepare the cerium-based abrasive slurry stock solution.

[0084] In order to suppress thickening caused by the addition of the above phosphoric acid compound, water is also added to the classification slurry along with the above phosphoric acid compound and mixed. The phosphoric acid compound may be dissolved in water and added.

[0085] The above mixing method is not particularly limited and only requires that the mixture be stirred to the extent that the phosphate compound can be dissolved in water. For example, mixing may be performed using a stirrer such as a high-speed shearer, or using a media mill such as a ball mill or a bead mill.

[0086] The cerium-based abrasive slurry stock solution obtained as described above may be prepared by adding additives, such as pH adjusters, defoaming agents, and rust inhibitors, as needed, within a range that does not impair the abrasive performance of the abrasive solution prepared using this.

[0087] [Polishing Fluid]

[0088] The above cerium-based abrasive slurry stock solution is diluted with water and prepared as a polishing solution depending on the polishing device used or the required polishing performance. In terms of providing good polishing performance on glass materials and also in terms of cost, it is preferable that the TREO in the prepared solution be used in the range of 0.1 to 10.0 mass%, more preferably 0.5 to 9.0 mass%, and even more preferably 1.0 to 8.0 mass%.

[0089] In addition, the polishing solution may be prepared by adding additives, such as pH adjusters, antifoaming agents, and rust inhibitors, as necessary when preparing the polishing solution, taking into account the specifications of the polishing target or polishing device, within a range that does not interfere with the polishing performance of the polishing solution.

[0090] The polishing method using the above polishing liquid is not particularly limited, and methods using known polishing devices, etc., may be applied. The above polishing liquid can be used in a known manner, for example, when performing finishing polishing such as mirror polishing of glass materials using a single-sided polisher or a double-sided polisher.

[0091] The above cerium-based abrasive slurry stock solution has excellent productivity, and the polishing solution prepared using it has good polishing performance for glass materials, and in particular, it can be used for finishing polishing of various glass materials and glass products, such as glass substrates for magnetic disks, glass substrates for liquid crystal displays, glass substrates for color filters or photomasks, and glass substrates for optical lenses.

[0092] Examples

[0093] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.

[0094] In addition, the content of TREO and heavy rare earth oxides in the following examples and comparative examples, the content of Ce oxides relative to TREO (Ce amount / TREO), and the fluorine atom content were determined as follows.

[0095] [TREO]

[0096] Water ammonia was added to the acid-dissolved solution of the measurement sample. The resulting precipitate was filtered and washed to remove alkali metals, and then dissolved in acid again. Oxalic acid was added to this solution, and the resulting precipitate was calcined in the atmosphere to determine TREO by gravimetric method.

[0097] [Content in Oxide Conversion of Heavy Rare Earths]

[0098] The measurement sample was dissolved in acid, the amount of each rare earth element was measured using the ICP-AES method, and the value was obtained by summing the values ​​converted to oxides for heavy rare earths.

[0099] [Ce Amount / TREO]

[0100] The measurement sample was dissolved in acid, and the amount of Ce measured by the ICP-AES method was obtained by calculating the value of TREO converted into oxides.

[0101] [Fluorine atomic content]

[0102] The measurement sample (mixed rare earth oxide particles) was alkaline melted and extracted with hot water, and measured using a fluoride ion meter (manufactured by HORIBA, Ltd.; ion electrode method). In addition, it was assumed that the anionic water-soluble polymer, the phosphate compound, and the water did not contain fluoride atoms, and the fluoride atom content in the abrasive slurry was estimated from the fluoride atom content in the mixed rare earth oxide particles used in the preparation of the cerium-based abrasive slurry stock solution.

[0103] [Preparation of Cerium-based Abrasive Slurry Stock Solution]

[0104] (Example 1)

[0105] A rare earth concentrate (ore) containing 47.0 mass% of TREO and 2.0 mass% of heavy rare earth in terms of oxides was treated by sulfuric acid roasting and solvent extraction methods, thereby reducing impurities other than rare earth elements to 1.0 mass% or less and heavy rare earth to 1.0 mass% or less in terms of oxides, and obtaining a mixed light rare earth compound with adjusted rare earth element content. This mixed light rare earth compound was carbonated using ammonium bicarbonate to form a mixed rare earth carbonate, and then the mixed rare earth carbonate was calcined in an electric furnace in the atmosphere at 900°C for 10 hours to obtain mixed rare earth oxide particles (D 50 :10㎛). Among the above mixed rare earth oxide particles, TREO was 97.0 mass% and the fluorine atom content was 0 mass%.

[0106] To 5000g of the above mixed rare earth oxide particles, 3475g of soft water and a sodium salt of a copolymer of acrylic acid and maleic acid as an anionic water-soluble polymer ("Poise (registered trademark) 521" manufactured by Kao Corporation, an aqueous solution with a solid content concentration of 40 mass% (solid content is considered as a polymer component); "AA-MA" in Table 1) were added in an amount of 4.1 mass (converted to solid content) per 100 mass parts of TREO in the above mixed rare earth oxide particles (mixed rare earth oxide particle concentration 55.7 mass%), and the mixture was ground for 3 hours using a bead mill (beads: made of zirconia, diameter 0.3mm; mill peripheral speed 8m / s) to obtain a ground slurry.

[0107] The above-mentioned crushed slurry was wet-classified to remove coarse particles (particle size greater than 5.0 μm) and obtain a classified slurry. A phosphoric acid compound (sodium tripolyphosphate) was dissolved in soft water and added to the classified slurry at a mixing amount of 4.1 parts by mass per 100 parts by mass of TREO in the mixed rare earth oxide particles, and stirred and mixed to produce a cerium-based abrasive slurry stock solution having a TREO content of 23.1 mass%.

[0108] (Examples 2–10 and Comparative Examples 1–5)

[0109] A cerium-based abrasive slurry stock solution was prepared using the raw material composition shown in Table 1 below and in the same manner as in Example 1.

[0110] In addition, "AA" in the anionic water-soluble polymer in Table 1 refers to the sodium salt of polyacrylic acid ("Poise (registered trademark) 530, manufactured by Kao Corporation, aqueous solution with a solid content of 40 mass% (solid content is considered as a polymer component)). Also, the notation "-" indicates that it is not added.

[0111] [Evaluation Measurement]

[0112] The following evaluation measurements were performed on the cerium-based abrasive slurry stock solution prepared in the above examples and comparative examples. In addition, the polishing performance was evaluated using a polishing solution prepared by diluting the cerium-based abrasive slurry stock solution with pure water.

[0113] The results of their evaluation measurements are summarized in Table 1 below.

[0114] [D 50 ]

[0115] Using the Microtrack particle size analyzer “MT3300II” (manufactured by Nikkiso Co., Ltd.), the particle size distribution of slurry particles was measured by the laser diffraction scattering method, and the particle diameter at 50% of the cumulative volume (D 50 saved )

[0116] [Productivity]

[0117] In the preparation of cerium-based abrasive slurry stock solution, the workload in preparing the grinding slurry is the greatest and has a significant impact on productivity, so the following evaluation of the process of obtaining the grinding slurry was considered as an evaluation of productivity.

[0118] The upper limit concentration of mixed rare earth oxide particles that can obtain a crushed slurry without the internal pressure and temperature of the bead mill rising (internal pressure 0.3 MPa or less, temperature 55°C or less) was investigated, and based on the upper limit concentration, an evaluation was performed according to the following evaluation criteria.

[0119] (metewand)

[0120] A: Concentration 55 mass% or higher

[0121] B: Concentration 50 mass% or more and less than 55 mass%

[0122] C: Concentration 40 mass% or more and less than 50 mass%

[0123] D: Concentration less than 40 mass%

[0124] In the case of evaluations A and B, productivity is said to be excellent. On the other hand, in the case of evaluations C and D, productivity was judged to be poor.

[0125] [Grinding Performance]

[0126] A cerium-based abrasive slurry stock solution was diluted with pure water to prepare a polishing solution containing 5.0 mass% TREO. Using this polishing solution, a polishing test was performed with a single-sided polisher under the following polishing conditions, and the polishing speed and surface roughness (arithmetic mean roughness Ra) were measured as follows.

[0127] The polishing speed was determined by measuring the sample thickness before and after polishing at four locations per sample using a micrometer and calculating the arithmetic mean value.

[0128] Surface roughness (Ra) was determined by measuring the polished surface of the sample after polishing for 120 minutes using a stylus profiler ("P-12", manufactured by KLA-Tencor).

[0129] <Grinding Conditions>

[0130] Sample to be polished: Commercially available blue glass (50mm × 50mm × thickness 1.10mm, polishing area 25cm) 2 )

[0131] Polishing pad: Suede pad

[0132] Lower platen rotation speed: 260 rpm

[0133] Pressure during grinding: 80g / cm² 2

[0134]

[0135] As can be seen from Table 1, it was confirmed that the cerium-based abrasive slurry stock solution (Examples 1 to 10) of a predetermined particle size, prepared by combining a predetermined amount of anionic water-soluble polymer and a phosphate compound, has excellent productivity. In addition, it was confirmed that when using a polishing solution diluted with the above cerium-based abrasive slurry stock solution, the polishing speed does not decrease even after 120 minutes of polishing time, the polishing power is maintained, and polishing can be performed with good surface roughness (Ra) (processing precision).

[0136] From this, it is said that the cerium-based abrasive slurry stock solution of the present embodiment can improve productivity and also provide a polishing solution that exhibits good polishing performance on glass materials.

Claims

Claim 1 A cerium-based abrasive slurry stock solution comprising mixed rare earth oxide particles and water, wherein the cerium-based abrasive slurry stock solution comprises an anionic water-soluble polymer and a phosphate compound, the oxide equivalent content of the total rare earth element (TREO) is 10.0 to 40.0 mass%, the oxide equivalent content of cerium in the TREO is 50.0 mass% or more, the content of the anionic water-soluble polymer is 1.5 to 10.0 mass parts per 100 mass parts of the TREO, and the particle size (D) at 50% of the cumulative volume in the particle size distribution by laser diffraction scattering of the slurry particles 50 ) is 0.10 to 0.35 μm, and the above anionic water-soluble polymer is a cerium-based abrasive slurry stock solution in which the polycarboxylic acid-based polymer is a polycarboxylic acid-based polymer. Claim 2 A cerium-based abrasive slurry stock solution according to claim 1, wherein the polycarboxylic acid-based polymer is one or more selected from polyacrylic acid, a copolymer of acrylic acid and maleic acid, and alkali metal salts thereof. Claim 3 A cerium-based abrasive slurry stock solution, wherein the phosphoric acid compound is one or more selected from tripolyphosphoric acid, pyrophosphoric acid, hexametaphosphoric acid, and alkali metal salts thereof. Claim 4 A cerium-based abrasive slurry stock solution according to claim 1, wherein the content of the phosphoric acid compound is 0.5 to 10.0 parts by mass per 100 parts by mass of TREO. Claim 5 A method for manufacturing a cerium-based abrasive slurry stock solution according to claim 1, comprising: a process of wet-grinding a mixed raw material comprising the mixed rare earth oxide particles, water, and the anionic water-soluble polymer to obtain a ground slurry; a process of wet-classifying the ground slurry to obtain a classified slurry; and a process of adding water and the phosphoric acid compound to the classified slurry and mixing to obtain the cerium-based abrasive slurry stock solution. Claim 6 A polishing solution in which the cerium-based abrasive slurry stock solution described in claim 1 is diluted with water, and the TREO is 0.1 to 10.0 mass%. Claim 7 A cerium-based abrasive slurry stock solution comprising mixed rare earth oxide particles and water, wherein the cerium-based abrasive slurry stock solution comprises an anionic water-soluble polymer and a phosphate compound, the oxide equivalent content of the total rare earth element (TREO) is 10.0 to 40.0 mass%, the oxide equivalent content of cerium in the TREO is 50.0 mass% or more, the content of the anionic water-soluble polymer is 1.5 to 10.0 mass parts per 100 mass parts of the TREO, and the particle size (D) at 50% of the cumulative volume in the particle size distribution by laser diffraction scattering of the slurry particles 50 ) is 0.10 to 0.35 μm, the fluorine atom content is 0.1 mass% or less, and the anionic water-soluble polymer is a polycarboxylic acid-based polymer, a cerium-based abrasive slurry stock solution. Claim 8 delete Claim 9 delete

Citation Information

Patent Citations

  • Cerium oxide-based polishing agent and method for manufacturing hard disk substrate made of glass

    JP2012038361A

  • CMP polishing compound

    KR1020080067715A

  • CMP slurry and polishing method using the same

    KR1020090096318A

  • CMP polishing liquid, method for polishing substrate, and electronic component

    KR1020120135921A

  • Ceriuim-based abrasive material and process for producing same

    KR1020180042375A